Literature Review and Clinical Presentation of Bilateral Acetabular Fractures Secondary to Seizure Attacks - Alexandre H. Nehme; Jihad F. Matta; Alaa G. Boughannam; Fouad C. Jabbour; Joseph Imad; Ramzi Moucharafieh (Case Reports in Orthopedics)
Central acetabular fracture dislocation is usually caused by high-energy external trauma. However, 26 cases that occurred as a result of a seizure attack appeared in the literature from 1970 to 2007, with the seizure attacks themselves caused by many different factors. In this setting, the central acetabular fracture not caused by direct trauma might initially remain unnoticed leading to a delayed diagnosis. In some cases, this may lead to death as a result of massive blood loss. We here present a case of bilateral central acetabular fracture dislocation as a result of a seizure attack.